KEMENANGAN BIDEN DAN MASA DEPAN POLITIK RASISME AMERIKA SERIKAT - Dairatul Ma’arif; Muhadjir Muhadjir; Hino Samuel Jose (Universitas Wahid Hasyim Semarang, 2022)
The United States is a country with a high level of racial discrimination. Racism has taken root and has become a very serious issue for the US nation. Even in the Trump era, the problem of racism is at its worst level in the modern history of the US nation. The issue of racism itself has been a major factor in Biden's victory in the US presidential election. And Biden's victory is inseparable from the multi-ethnic support that rejects Trump's political practices and racist rhetoric. Biden is considered capable of achieving racial equality despite the legacy of extreme inequality and high racial upheaval by the previous administration. By using qualitative methods, this study aims to elaborate on the extent of Biden's victory and the future of racism politics in the US. And the finding in this study is that Biden has contributed significantly to realizing racial equality in the US. Through his racial equality policies, Biden has succeeded in reducing the level of systemic racism in the US. The racial equality policies that are embodied in the form of an executive order include; Fair Housing Policy, Incarceration Reform, Reaffirm the Federal Government’s Commitment to Tribal Sovereignty and Consultation, and Memorandum Condemning and Combating Racism, Xenophobia, and Intolerance Against Asian Americans and Pacific Islanders in the United State. Keywords: Racism, Biden, Racial Equality, Executive Order, TrumpAbstrakAmerika Serikat adalah negara dengan tingkat diskriminasi rasial yang tinggi. Rasisme telah mengakar dan menjadi isu yang sangat serius bagi bangsa AS. Bahkan di era Trump, masalah rasisme berada pada level terburuk dalam sejarah modern bangsa AS. Isu rasisme sendiri menjadi faktor utama kemenangan Biden dalam pemilihan presiden AS. Dan kemenangan Biden tidak terlepas dari dukungan multi etnis yang menolak praktik politik Trump dan retorika rasis. Biden dianggap mampu mencapai kesetaraan rasial meskipun warisan ketidaksetaraan ekstrem dan pergolakan rasial yang tinggi oleh pemerintahan sebelumnya. Dengan menggunakan metode kualitatif, penelitian ini bertujuan untuk mengelaborasi sejauh mana kemenangan Biden dan masa depan politik rasisme di AS. Dan temuan dalam penelitian ini adalah bahwa Biden telah berkontribusi secara signifikan untuk mewujudkan kesetaraan ras di AS. Melalui kebijakan kesetaraan rasnya, Biden berhasil menurunkan tingkat rasisme sistemik di AS. Kebijakan kesetaraan ras yang diwujudkan dalam bentuk perintah eksekutif meliputi; Kebijakan Perumahan yang Adil, Reformasi Pemenjaraan, Menegaskan Kembali Komitmen Pemerintah Federal untuk Kedaulatan dan Konsultasi Suku, dan Memorandum Mengutuk dan Memerangi Rasisme, Xenofobia, dan Intoleransi Terhadap Orang Asia-Amerika dan Penduduk Kepulauan Pasifik di Amerika Serikat.Kata kunci: Rasisme, Biden, Kesetaraan Rasial, Perintah Eksekutif, Trump